Language policy and practices in Indonesian higher education institutions - Lotfie, Maskanah Mohammad; Hartono, . (IIUM Press, International Islamic University Malaysia, 2018)
English in Indonesia has foreign language status. Nevertheless, the language is greatly significant to the country due to its numerous regional and global appeals. The current language policy of Indonesia ensures that the language is taught to children from junior high school level. However, as a reflection of a language that has not been prioritised in school curriculum, school leavers largely have limited grasp of the language by the time they enrol into university programmes. This study attempts to highlight institutional practices in student enrolment into and graduation from English programmes. It is also concerned with issues that are perceived to have derived from the policy. Based on interviews with 23 academics from five universities in Central Java, the majority of whom are administrators, policy-related issues of the English language are identified in this paper. Findings include communication skill difficulties faced by English majors and the juxtaposition of state and private universities in terms of student recruitment. The findings are significant in informing stakeholders such as policy makers, administrators, language instructors, and other practitioners about the impact of language policy and planning on practices in higher education institutions in Central Java and in assisting future decision-making processes whereby the consequences are far reaching.